An offline scheme for reducing cost of protection in all-optical WDM mesh networks with fast recovery. Issue 5 (3rd September 2019) - Dey, Vishal; Bandyopadhyay, Abhishek; Bhattacharya, Uma; Chatterjee, Monish
ABSTRACT: In Optical WDM networks, a single fiber carries enormous amount of data and consequently designing schemes to prevent the user traffic from disruption and techniques to recover from failures still remains an important area of research. In this paper we address the problem of protecting all - optical WDM mesh networks from single link failure. We propose an offline protection scheme that is not only cost-efficient in terms of network resource consumption but can also provide quick recovery from a link failure. In our scheme, backup paths are combined to reduce cost of protection and to facilitate fast recovery from a failure. We address a critical issue related to selection of backup paths to be combined, which was not addressed earlier. Instead of choosing backup paths for connection requests arbitrary as done in an existing scheme, our scheme is designed to select backup paths in a way that they are suitable for combination and can maximize resource saving as well. We first provide an Integer Linear Program for the problem, and then propose a heuristic eStreams that can provide near optimal solution in polynomial time. Performance comparisons with some well-known schemes show that our protection scheme is definitely an improvement in terms resource conservation while ensuring fast recovery from a link failure. The figure shows how a primary (working) path is protected with the help of a link-disjoint backup path in WDM optical networks. A primary path is used to carry traffic under normal fault free condition. In the event of a link fault (fiber-cut) the traffic is switched over to the backup path. GRAPHICAL ABSTRACT: